Islamic Organizational Communications in Delivering Motivation to Youth in Pitumpanua, Wajo Regency - Elfrianto, Elfrianto; Sultan, M. Iqbal; Bahfiarti, Tuti (International Journal of Demos (IJD), 2022)
AbstractThis study aims to examine the communication of the Islamic Organization of DDI in motivating Pitumpanua teenagers. The local community well received the DDI organization in Pitumpanua. DDI responds to the phenomenon of many people dropping out of education and the many religious movements that are intolerant of differences. Similar to other social organizations equipped with autonomous bodies and institutions within the DDI organization, some play a role and are instrumental in its development. However, according to Islamic law, the DDI organization is identical to the education and daâ€™wah movement. The research method used in this paper is a qualitative descriptive method, and the researcher is the crucial instrument in the research. The results of this study indicate that DDI contributes to making teenagers aware of the importance of learning Islamic religious education as a motivation to have a strong foundation in themselves to achieve a better future.Keywords: DDI Pitumpanua, Youth Education Motivation, Organizational Communication.Â AbstrakPenelitian ini bertujuan untuk mengkaji komunikasi Ormas DDI dalam memotivasi remaja Pitumpanua. Masyarakat setempat menyambut baik organisasi DDI di Pitumpanua. DDI merespon fenomena banyaknya masyarakat putus sekolah dan banyaknya gerakan keagamaan yang tidak toleran terhadap perbedaan. Serupa dengan organisasi sosial lainnya yang dilengkapi dengan badan dan lembaga otonom di dalam organisasi DDI, beberapa berperan dan berperan dalam perkembangannya. Namun, menurut hukum Islam, organisasi DDI identik dengan gerakan pendidikan dan dakwah. Metode penelitian yang digunakan dalam tulisan ini adalah metode deskriptif kualitatif, dan peneliti merupakan instrumen penting dalam penelitian. Hasil penelitian ini menunjukkan bahwa DDI berkontribusi untuk menyadarkan remaja akan pentingnya mempelajari pendidikan agama Islam sebagai motivasi untuk memiliki landasan yang kuat dalam diri mereka untuk meraih masa depan yang lebih baik.Kata kunci: DDI Pitumpanua, Motivasi Pendidikan Pemuda, Komunikasi Organisasi.